Nanozyme catalytic mimetic effect of iron oxide nanoparticles hybrids with cellulosic matrices and its synergism with microorganisms - Leonardo Zanata; Derval dos Santos Rosa (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2023)
Iron Oxide Nanoparticles (IONPs) are generally assumed to be biologically inert, presenting chemical stability and low toxicity, and they can be hybridized with cellulosic matrixes aiming for biological applications (e.g. nanozymes). Two hydrothermal coprecipitation methods were applied, aiming to produce 2 different size Iron oxide nanoclusters, using ferric chloride and ferrous chloride, as well as nitrocellulose and cellulosic residues for the hybrids. The obtained materials were tested for catalytic effect in comparison and in synergy with catalase-positive P. aeruginosa, S. aureus, and B. subtilis bacterial strains. The catalytic effect was observed for all obtained materials and microorganisms, Due to the bivalent and trivalent iron molecules distributed along IONP cubic crystalline inverse spinel structures. Michaelis-Menten constant (Km) of IONP-and hybrids was higher in synergy with S. aureus in comparison with the results obtained by the microorganism alone, for instance, the best enzymatic efficiency for O2 release from hydrogen peroxide among the tested microorganisms. However, no significant difference was observed for most of the obtained materials alone. On the other hand, IONPs may help microorganisms as mimetic catalytic enzymes, when applied in synergy whit them.